2018
DOI: 10.1111/cbdd.13318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, activity, and docking studies of eugenol‐based glucosides as new agents against Candida sp.

Abstract: Seventeen new synthetic derivatives of eugenol (6, 8-15 and 8'-15') were planned following literature reports on antifungal activities of nitroeugenol and eugenol glucoside. The anti-Candida activity of these compounds was investigated by in vitro assay, and the cytotoxicity evaluation was performed with the most active compounds. The peracetylated glucosides presented better biological results than their hydroxylated analogues. The glucoside 11, a 4-nitrobenzamide, showed the best potency (MIC range 11.0-151.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
(36 reference statements)
1
19
1
Order By: Relevance
“…Therefore, modification of its chemical structure is sought out to be an important strategy to obtain molecules with desirable physicochemical and improved biological properties 5,9,10 . The enhanced antimicrobial activity of eugenol by its derivatisation has already been reported [11][12][13] . Recently, new Mannich base-type derivatives of eugenol were found to possess antifungal activity even equivalent to fluconazole 14 .…”
mentioning
confidence: 84%
“…Therefore, modification of its chemical structure is sought out to be an important strategy to obtain molecules with desirable physicochemical and improved biological properties 5,9,10 . The enhanced antimicrobial activity of eugenol by its derivatisation has already been reported [11][12][13] . Recently, new Mannich base-type derivatives of eugenol were found to possess antifungal activity even equivalent to fluconazole 14 .…”
mentioning
confidence: 84%
“…Pharmacological properties of eugenol have been extensively highlighted, especially involving its antibacterial and antifungal properties [17–22] . Our research group has previously demonstrated that synthetic compounds obtained from natural phenylpropanoids, such as eugenol or its analogs (dihydroeugenol and isoeugenol), have important antimicrobial activity and that hybrids obtained from phenylpropanoids and sulfonamide moieties have important antitumor activity [23–30] . Taking advantage of the molecular hybridization strategy (and the well‐established antibacterial potential of eugenol and sulfonamide‐based drugs separately) herein we present for the first time the antibacterial activity of eugenol and dihydroeugenol‐based hybrids bearing the sulfonamide functionality ( Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1960s, there was a dramatic increase in fungal infections because of the development of antibiotic therapies (Vandeputte, Ferrari, & Coste, 2012), which represents a serious problem today. However, the number of antimicrobial medicines is limited, and it does not satisfy | 1187 JOAQUIM et Al. the need due to limitations related to the spectrum of action, potency, pharmacokinetic properties, and the emergent resistance of fungi and bacteria (Hipólito et al, 2018;Nett & Andes, 2016;Patil et al, 2018;Tobudic, Kratzer, & Presterl, 2012). In this context, the search and development of new antimicrobial therapies is imperative.…”
Section: Introductionmentioning
confidence: 99%